2013
DOI: 10.2478/v10288-012-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the catena concept in studies of landscape system dynamics

Abstract: The concept of catena in landscape surveys is used to demonstrate the surroundings of landscape units, their vertical structure and inter-unit processes, as well as the mosaic nature of the landscape. Furthermore, it reflects the structural and functional heterogeneity of the surveyed area, at the same time indicating types of links between landscape units, depending on a variety of geological, habitat-related and biotic conditions, including land use and its transformation arising from anthropopressure. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The above-mentioned study showed that soil properties are highly correlated with slope position (Karaca et al, 2018). Soil organic matter content has been reported to vary based on slope position, this likely a result of the catena concept which suggests that downhill movement of plant material due to gravity and water flow results in different soil characteristics between the hill summit and foothill (Malinowska & Szumacher, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The above-mentioned study showed that soil properties are highly correlated with slope position (Karaca et al, 2018). Soil organic matter content has been reported to vary based on slope position, this likely a result of the catena concept which suggests that downhill movement of plant material due to gravity and water flow results in different soil characteristics between the hill summit and foothill (Malinowska & Szumacher, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…The above‐mentioned study showed that soil properties are highly correlated with slope position (Karaca et al, 2018). Soil organic matter content has been reported to vary based on slope position, this likely a result of the catena concept which suggests that downhill movement of plant material due to gravity and water flow results in different soil characteristics between the hill summit and foothill (Malinowska & Szumacher, 2013). Therefore, there is a need for in‐depth understanding of how slope position shapes soil physico‐chemical properties and how these influence soil and vegetation recovery in oldfields targeted for ecological restoration.…”
Section: Introductionmentioning
confidence: 99%
“…each of which carries information about physical, chemical, and biological processes and parameters 3 . Sivash (Rotten Sea, Sivashi)a shallow lagoon-type bay in the western part of the Azov Seais located in the southern part of Ukraine in the area of transition of its main continental part to the peninsulathe Crimea.…”
mentioning
confidence: 99%